Цифровизация процессов обслуживания в библиотеках – это уже реальность - M. Yu. Neshcheret (Библиосфера)
The article considers theoretical issues of digitalization in libraries, characterizes modern forms and methods of providing library and information services, ways of communication between libraries and users. It reveals qualitatively new opportunities of library and information service due to spreading digital technologies and robotics in libraries. Cases of successful implementation of library and information services digitization projects demonstrate the library readiness to move to a new level of development. The author concludes that despite the fact that digitalization significantly increases services efficiency, effects positively on their quality and, consequently, attracts new users to libraries, library information services also include processes that are impossible without human participation with qualities such as the ability to anticipation, emotional experience, intuitive forecasting. Therefore, it is necessary to be aware of the boundaries and professional needs when using digital technologies in library and information services.